Electroencephalography Mu Rhythm Changes and Decreased Spasticity After Repetitive Peripheral Magnetic Stimulation in Patients Following Stroke - Chen, Shugeng; Li, Yang; Shu, Xiaokang; Wang, Chuankai; Wang, Hewei; Ding, Li; Jia, Jie (Frontiers in Neurology, 2020)
Background: Spasticity is common among patients with stroke. Repetitive peripheral magnetic stimulation (rPMS) is a painless and noninvasive therapy that is a promising approach to reducing spasticity. However, the central mechanism of this therapy remains unclear. Changes in cortical activity and decreased spasticity after rPMS intervention require further exploration. The aim of this study was to explore the electroencephalography (EEG) mu rhythm change and decrease in spasticity after rPMS intervention in patients with stroke. Materials and methods: A total of 32 patients with spasticity following stroke were recruited in this study and assigned to the rPMS group (n = 16) or sham group (n = 16). The modified Ashworth scale, modified Tardieu scale, and Fugl–Meyer assessment of the upper extremity were used to assess changes in upper limb spasticity and motor function. Before and after the rPMS intervention, EEG evaluation was performed to detect EEG mu rhythm changes in the brain. Results: After one session of rPMS intervention, spasticity was reduced in elbow flexors (p < 0.05) and wrist flexors (p < 0.05). Upper limb motor function measured according to the Fugl–Meyer assessment was improved (p < 0.05). In the rPMS group, the power of event-related desynchronization decreased in the mu rhythm band (8–12 Hz) in the contralesional hemisphere (p < 0.05). Conclusions: The results indicate that rPMS intervention reduced spasticity. Cortical activities changes may suggest this favorable change in terms of its neurological effects on the central nervous system.